Admiralty and maritime law - Schoenbaum, Thomas J.; McClellan, Jessica L. (St. Paul, MN : West, 2012)
Previous editions published : 4th (2004) and 1st (1987).
Admiralty jurisdiction -- Federalism and admiralty -- Admiralty and the general maritime law -- Seamen -- Longshore and harbor workers -- Wrongful death -- Carriage of goods -- Charter parties -- Towage -- Pilotage -- Collision and marine casualty -- Limitation of liability -- Salvage -- Admiralty practice and procedure.
Includes bibliographical references and index.
Kept up to date by pocket parts.
Keywords: Maritime law -- United States; Admiralty -- United States